2019
DOI: 10.1080/10934529.2018.1535160
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of copper and silver as residual disinfectants in drinking water

Abstract: Contamination events and biofilms can decrease the amount of free chlorine available in drinking water systems. The efficacy of 100 μg/L silver and 400 μg/L copper, individually and combined, were evaluated as secondary, longer-lasting residual disinfectants against Salmonella enterica serovar Typhimurium, Escherichia coli, Listeria monocytogenes, and Mycobacterium fortuitum at 24°C and 4°C. A >5.0-log10 reduction was observed in E. coli and L. monocytogenes after three hours and S. Typhimurium following seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…Recently, Cu nanoparticles (CuNPs) were shown to exhibit powerful anti-biofilm activity on pathogen bacteria such as Escherichia coli, Salmonella typhi, Shigella flexneri , and Pseudomonas aeruginosa , because cell death was mediated by massive destruction of the plasmatic cell membrane and the production of high concentrations of reactive oxygen species also known as ROS [ 33 ]. Similar results have also recently been published in terms of the use of Cu oxide (CuO) NPs [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 79%
“…Recently, Cu nanoparticles (CuNPs) were shown to exhibit powerful anti-biofilm activity on pathogen bacteria such as Escherichia coli, Salmonella typhi, Shigella flexneri , and Pseudomonas aeruginosa , because cell death was mediated by massive destruction of the plasmatic cell membrane and the production of high concentrations of reactive oxygen species also known as ROS [ 33 ]. Similar results have also recently been published in terms of the use of Cu oxide (CuO) NPs [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 79%
“…35 The residual metal ions in the water can also serve as a longterm disinfectant during the distribution of treated water to prevent target viruses from growing again. 36 Thus, the removal of MS-2 with Mag-PCMA-MI should not lead to additional environmental effects.…”
Section: Resultsmentioning
confidence: 99%
“…Although a small fraction of metal ions will leach into the water after removal (0.8% of adsorbed Ag + , 0.6% of adsorbed Cu 2+ , and 0.9% of adsorbed Fe 3+ ), the concentration of residual metal ions can be maintained below a safe level by adjusting the amount of metal ions coated onto Mag-PCMA during the sorption process . The residual metal ions in the water can also serve as a long-term disinfectant during the distribution of treated water to prevent target viruses from growing again . Thus, the removal of MS-2 with Mag-PCMA-MI should not lead to additional environmental effects.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Silver nitrate, copper sulfate, nitric acid, sulfuric acid, sodium hydroxide, sodium chloride and calcium carbonate were purchased from Fisher Scientific (USA). Ag + and Cu 2+ are selected as the metal ions disinfectants as they are commonly used as algaecides in many studies [3,27,29] and have demonstrated effectiveness. Our innovative approach allows the recovery of the metal ions for reuse, making it less expensive and more sustainable.…”
Section: Methodsmentioning
confidence: 99%